Association between persistent endocrine-disrupting chemicals (PBDEs, OH-PBDEs, PCBs, and PFASs) and biomarkers of inflammation and cellular aging during pregnancy and postpartum. (June 2018) - Zota, Ami R.; Geller, Ruth J.; Romano, Laura E.; Coleman-Phox, Kimberly; Adler, Nancy E.; Parry, Emily; Wang, Miaomiao; Park, June-Soo; Elmi, Angelo F.; Laraia, Barbara A.; Epel, Elissa S.
Abstract: Background: Endocrine-disrupting chemicals (EDCs) can target immune and metabolic pathways. However, few epidemiologic studies have examined the influence of EDCs on measures of inflammation and cellular aging during pregnancy and postpartum. Objective: We investigated associations between prenatal exposures to polybrominated diphenyl ethers (PBDEs), hydroxylated PBDE metabolites (OH-PBDEs), polychlorinated biphenyls (PCBs), and per- and polyfluorochemicals (PFASs) with repeated biomarker measurements of inflammation and cellular aging in women during pregnancy and the postpartum period. Methodology: Overweight or obese pregnant women were recruited from the San Francisco Bay area (n = 103) during their first or second trimester of pregnancy. Blood samples were collected from participants at baseline (median 16 weeks gestation) and at three and nine months postpartum. Serum concentrations of PBDEs, OH-PBDEs, PCBs, and PFASs were measured at baseline. Inflammation biomarkers (interleukin 6 [IL-6], interleukin 10 [IL-10], and tumor necrosis factor [TNF-α]) and leukocyte telomere length (LTL), a biomarker of cellular aging, were measured at all three time points. Associations between serum chemical concentrations and repeated measures of IL-6, IL-10, TNF-α, and LTL were examined using linear mixed models. We also examined the potential for effect modification by time (visit) and obesity. Results: In adjusted models, we observed positive relationships between PBDEs and pro-inflammatory cytokines (IL-6 and TNF-α). A doubling in ∑PBDEs was associated with a 15.26% (95% CI 1.24, 31.22) and 3.74% (95% CI −0.19, 7.82) increase in IL-6 and TNF-α, respectively. Positive associations were also observed for PFASs and IL-6. A two-fold increase in ∑PFASs was associated with a 20.87% (95% CI 3.46, 41.22) increase in IL-6. 5-OHBDE-47 was inversely associated with anti-inflammatory cytokine IL-10. Some EDC-outcome associations, including those of PBDEs with TNF-α, were stronger during pregnancy (compared to three or nine months postpartum) and among obese (compared to overweight) women (p-interaction <0.05). Conclusions: These findings suggest that exposure to specific EDCs is associated with increased inflammation among women during pregnancy and the postpartum period. Future studies should replicate these findings in additional study populations and examine the implications of these associations for maternal and child health. Highlights: Serum levels of PBDE congeners and their metabolites may increase inflammation in pregnant and postpartum women. Serum levels of PFAS chemicals may increase inflammation in pregnant and postpartum women. Obesity may exaggerate the effects of environmental chemicals on inflammation during pregnancy and postpartum.